FAKTOR DETERMINAN PERKEMBANGAN FISIK PINGGIRAN KOTA SEMARANG TAHUN 1980-2000 - Hariyanto Hariyanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The research was conducted on the outskirts of Semarang. The area was chosen because it has been undergoing a rapid development as marked by urban sprawl towards the outside. The complex physiographical condition of the city of Semarang has caused an uneven sprawl. 111e main areas of investigation were the patterns, processes, intensity, tendencies and other factors that contributed to the sprawl. The research methods used were: I. Map analysis by comparation of the maps of 1980 and 2000 in oreder to discover the patterns, processes an tendencies of the city's urban sprawl; 2. Library research by comparing land uses in 1980 and 2000 in order to discover the intensity of the sprawl; 3. field survey using questionnaires completed by household heads living in sprawling area. Samples were taken in stages: fisrt from cluster area to represent the eastern, south tern and western part of the outkirts; then a poprposive sample of I 00 household heads and 11 developers. The result ofthe research indicates Three kinds of processes were noted in the sprawl: concentric, ribbon, and leapfrog. The sprawling process in the eastern outkirts with a plain topography has concentric and ribbon patterns. The southerns outkirts with a wavy to rough topography has concentric, ribbon and leapfrog patterns. A concentric pattern is also found in a rough topography (Tembalang). This is caused by the the residents preference to live in the immediate vicinity of'an activity centre (such as a university campus). This phenomenon proves that urban sprawl correlates positively to the availability of existing invesment. The western outkirts has ribbon at long road Pantura and leapfrog patterns. The intensity of the urban sprawl in term of the change in the size of the settlement area is 231,9 ha/year. The largest land conversion covers ricefields (2,239.5 ha), marshland (435.46 ha), and dry fields (339.14 ha) during the years 1983-2000. The following determinant factors list in order ofsignificant influence: 1. Population growth, 2. The area's physical condition, 3. Socio-economic condition, 4. Availability ofpubilc utilities, 5 Accessibilty, 6. The government policy.